SENGKETA HAK ATAS TANAH MELALUI AKTA CESSIE: Studi Kasus Putusan Mahkamah Agung NO 308/PK/PDT2016 jo Kasasi NO 1625 K/PDT/2014 - David Simatupang (to-ra, 2020)
As a material right, land rights are land tenure rights that contain a series of authority, obligations and / or prohibitions for the right-holders to do something about the land that is claimed. "Something" that may, mandatory or prohibited to be done can be switched and switched. Land Rights can also be given a burden A land right will change if the ownership is transferred to another person through a legal act, and also switches due to the occurrence of a certain legal event, such as inheritance while the transfer by legal action can be like the submission of credit or transfer of receivables on a name like cessie In Indonesian Agrarian Law, there is a difference between the transfer of land rights and the imposition of land rights. This research aims to find out the Transfer of Receivables / Cessie can be transferred in Indonesia and the consequences of the Cessie law if carried out in the transfer of land rights using a case approach in court with Case Number 1625/K/PDT/2014. Keywords: Disputes; Land Rights and The Cessie.